The Influence of Information Asymmetry and Managerial Ownership on the Value of the Company (A Case Study on Manufacturing Companies Listed on the Indonesia Stock Exchange from 2019-2021) - Gracia Margaretha Damanik; Dinda Putri Irawan; Mohd. Nawi Purba; M. Ikbar Pratama (Kusuma Negara Business School, 2023)
The increasing value of a company is something that is aimed for when establishing a company, and this is done for the prosperity of the shareholders. Shareholders will also experience an increase in well-being when the value of a company's stock rises. A company's value increases when there's a reduction in information asymmetry (imbalance), allowing the company to have complete information about itself. The following research aims to analyze the influence of information asymmetry and managerial ownership on a company (Case Study on Manufacturing Companies listed on the IDX in 2019-2021). The method used in this research is quantitative, and the type of research is descriptive quantitative. The sample for this study includes 55 companies selected based on certain considerations over three years, 2019-2021, totaling 252 research samples. This research found that the value of manufacturing companies registered in the IDX from 2019-2021 is positively and partially influenced by information asymmetry and managerial ownership. Management and institutions should balance their share ownership in a company. In doing so, there will be no creation of minority and majority sides, making all shareholders equally responsible for selecting programs/plans to increase management utility, resulting in an increase in company value by both parties. As a result, this triggers an increase in the disclosure of social responsibility followed by an increase in the company's value.